Spontaneous bacterial peritonitis: How to deal with this life-threatening cirrhosis complication? - Tarsila CR Ribeiro; Julio MF Chebli; Mario Kondo; Pedro Duarte Gaburri; Liliana Andrade Chebli; Ana Cristina Amaral Feldner (Dove Medical Press, 2008)
Tarsila CR Ribeiro1, Julio MF Chebli2, Mario Kondo1, Pedro Duarte Gaburri3, Liliana Andrade Chebli2, Ana Cristina Amaral Feldner11Division of Gastroenterology, Department of Medicine of University Federal de São Paulo, UNIFESP, EPM, São Paulo, São Paulo, Brazil; 2Division of Gastroenterology, Department of Medicine of University Federal de Juiz de Fora, UFJF, Juiz de Fora, Minas Gerais, Brazil; 3Liver Unit Coordinator of Santa Casa de Misericórdia de Juiz de Fora, Minas Gerais, BrazilAbstract: Spontaneous bacterial peritonitis (SBP) is one of the most common and life-threatening complications of cirrhosis. It occurs in 10% to 30% of patients admitted to hospital and recent studies tend to demonstrate that SBP incidence seems to be decreasing in its frequency. A bacterial overgrowth with translocation through the increased permeable small intestinal wall and impaired defense mechanisms is considered to be the main mechanism associated with its occurrence. The Gram-negative aerobic bacteria are the major responsible for SBP episodes and Gram-positive bacteria, mainly Staphylococcus aureus, are being considered an emergent agent causing SBP. The prompt diagnosis of SBP is the key factor for reduction observed in mortality rates in recent years. The clinical diagnosis of SBP is neither sensitive nor specific and the search for new practical and available tools for a rapid diagnosis of SBP is an important endpoint of current studies. Reagent strips were considered a promising and faster way of SBP diagnosis. The prompt use of empirical antibiotics, mostly cefotaxime, improves significantly the short-term prognosis of cirrhotic patients with SBP. The recurrence rate of SBP is high and antibiotic prophylaxis has been recommended in high-risk settings. Unfortunately, the long-term prognosis remains poor.Keywords: cirrhosis, ascites, diagnosis, peritonitis, treatment